Detecting the most appropriate delay analysis methods for mega airport projects - Cevikbas, Murat; Isik, Zeynep (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose This study aims to detect the most appropriate delay analysis method in mega airport projects. Design/methodology/approach First, the criteria affecting the selection of delay analysis methods were detected through an in-depth literature review and an expert panel, which was conducted with 12 experts who have experience in delay analysis domain in mega airport projects. Later, fuzzy VIKOR (VIsekriterijumska optimizacija i KOmpromisno Resenje) approach was conducted by considering the detected selection criteria and the most common delay analysis methods. Findings Windows Analysis method was detected as the best option for mega airport projects. It was followed by Time Impact Analysis (TIA), collapsed as-built analysis, as-planned vs as-built method and impacted as-planned method, respectively. Originality/value Each project has its own characteristics and thus requires specific management techniques; therefore, selecting a delay analysis method without considering the project types and size may cause conflicts between the contracting parties. On the one hand, numerous fruitful studies concerning delay analysis methods have been conducted in the literature, but on the other hand, none of them has considered project characteristics in terms of project size and type while selecting the most appropriate delay analysis method. Moreover, the larger the size of a project is, the more vulnerable it is to encounter with delays. Mega airport construction projects are complex in their nature in that they are large size and involve multi-disciplinary processes; thus, they need special attention in the process of resolving delays. This study intended to fill this gap in the literature by focusing on selection of the most appropriate delay analysis method for mega airport projects, and it is clear that considering the project type and size in the selection of delay analysis methods will provide more reliable outcomes.
Keywords: Delay analysis; Windows Analysis; Airport project; Fuzzy; VIKOR; Construction; CONSTRUCTION PROJECTS; FUZZY VIKOR; Engineering; Business & Economics